Sensitivity of terrestrial carbon cycle to changes in precipitation regimes. (June 2020) - Wang, Zhipeng; He, Yongtao; Niu, Ben; Wu, Jianshuang; Zhang, Xianzhou; Zu, Jiaxing; Huang, Ke; Li, Meng; Cao, Yanan; Zhang, Yanjie; Chen, Ning; Yang, Shuai; et al.
Highlights: Annual precipitation and its monthly distribution were analyzed globally. The relative importance of altered precipitation on carbon cycle was quantified. The anomalies of GPP/NEP in most biomes mainly explained by annual precipitation. Monthly distribution play an important, even dominant role in some specific biomes. Abstract: Climate change critically affects the carbon cycle of terrestrial ecosystems and thereafter the climate-carbon feedback. Previous studies have addressed the changes in temporal and spatial distribution of precipitation, termed as altered precipitation regimes. However, the response of terrestrial carbon cycle to the changes remain unclear. In this study, we used three process-based models to investigate the effect of changes in precipitation regimes on interannual variability (IAV) of gross primary productivity (GPP), net ecosystem productivity (NEP) and ecosystem respiration (RE). Annual sum of precipitation (PRE) and its monthly distribution, including its uniformity (PCI, precipitation concentration index) and timing (PCT, precipitation center time index), were used to describe the changes in precipitation regimes. Our results showed that the anomalies of both GPP and NEP in most biomes can be dominantly explained by anomalies of PRE. In addition, we also found that PCI and PCT were responsible for carbon dynamics in some specific biomes. For example, PCI dominated anomalies of both GPP and NEP in evergreen broadleaf forests (EBF), and a lower PCI (more uniform) is conducive to the increase of GPP and NEP. PCT is critical in driving the anomaly of GPP in mix forest (MF), grassland (GRA) and barren vegetation (Barren), and more precipitation distributed in early growing season benefits the increase of GPP. The sensibility of carbon cycle to changes in precipitation is biome specific, being likely due to the mismatch between water use ratio (WUR, defined as the ratio of transpiration to evapotranspiration) and precipitation distribution, implying that changes in distribution of precipitation among seasons/months may change the water availability. Our findings highlighted the necessity to pay more attention to the effects of altered precipitation distribution on changes in ecosystem multifunctionality related to carbon cycle.